Metabolism, Metabolomics, and Nutritional Support of Patients with Sepsis - Englert, Joshua A; Rogers, Angela J (Clinics in chest medicine, 2016)
Sepsis is characterized by profound changes in systemic and cellular metabolism that disrupt normal metabolic homeostasis. These metabolic changes can serve as biomarkers for disease severity. Lactate, a metabolite of anaerobic metabolism, is the most widely used ICU biomarker and it is incorporated into multiple management algorithms. Technological advances now make broader metabolic profiling possible, with early studies identifying metabolic changes associated with sepsis mortality. Finally, given the marked changes in metabolism in sepsis and the association of worse prognosis in patients with severe metabolic derangements, we summarize the seminal trials conducted to optimize nutrition in the ICU.